Features of investigation of destruction or damage of vegetables - Oliynychuk, Roman (Actual problems of law (Aktual'ni problemi pravoznavstva), 2021)
Destruction or damage of flora is considered a crime against the environment. Researchers' views on the categories related to the investigation of this offense are analyzed. The importance of proper planning of actions of law enforcement officials for the successful detection of crimes against the environment committed by destroying or damaging flora is substantiated. The peculiarities of individual investigative actions in the investigation of the destruction or damage of flora are identified and the relevant author's conclusions are made.